The Weak Small RNA-Binding Activity of the 2b Proteins of Subgroup II Cucumber Mosaic Virus Strains Is Insufficient for RNA Silencing Suppression - Gao, Yingying; Yang, Jinrui; Zhang, Xiaobei; Chen, Aizhong; Gu, Zhouhang; Du, Zhiyou (Frontiers in Microbiology, 2021)
The 2b proteins encoded by cucumber mosaic virus (CMV) Subgroup I strains suppress RNA silencing primarily by competitively binding small RNAs (sRNAs) in the host cell cytoplasm. Interestingly, 2b proteins encoded by CMV Subgroup II strains accumulate predominantly in nuclei. Here we determined that whereas the 2b protein (Fny2b) of Subgroup IA strain Fny-CMV is highly effective in suppressing both sense RNA-induced and inverted repeat-induced post-transcriptional gene silencing (PTGS), the 2b protein (LS2b) of the Subgroup II strain LS-CMV was not as effective. Reducing nuclear accumulation of LS2b by mutating a residue in its nuclear localization sequence had no effect on RNA silencing suppressor activity, while attenuated viral symptoms. Electrophoretic mobility shift assays showed that the sRNA binding of LS2b was weaker and more selective than that of Fny2b. The domain determining the differential sRNA binding ability was delimited to the putative helix α1 region. Moreover, LS2b mutants that completely lost suppressor activity still retained weak sRNA binding ability, suggesting that sRNA binding is not sufficient for LS2b to suppress RNA silencing. Considering the Subgroup I strain-encoded 2b proteins that require sRNA binding ability for suppression of RNA silencing, we suggest that in addition to binding sRNA, the 2b proteins of Subgroup II CMV strains would require extra biological activities to achieve RNA silencing inhibition.